Keterampilan Mengelola Kelas - Putri Kesawan; Kholidah Nur; Rosmidar Rosmidar (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Class management skills are one of the basic abilities that an educator must have in creating a conducive learning environment. In the context of the Micro Teaching course, these skills include the ability to design classroom management strategies, create an atmosphere that supports learning, and overcome various challenges that arise in the classroom. The application of these skills includes time management, spatial planning, managing student interactions, and the ability to deal with student behavior effectively. Students are trained to apply various approaches in managing classes, such as preventive, corrective and supportive approaches, which aim to support the creation of an optimal learning process. With good classroom management skills, it is hoped that prospective teachers can build positive relationships with students, motivate active participation, and improve the quality of learning at various levels of education.